Comparison of high-flow nasal cannula versus oxygen face mask for environmental bacterial contamination in critically ill pneumonia patients: a randomized controlled crossover trial. Issue 1 (January 2019) - Leung, C.C.H.; Joynt, G.M.; Gomersall, C.D.; Wong, W.T.; Lee, A.; Ling, L.; Chan, P.K.S.; Lui, P.C.W.; Tsoi, P.C.Y.; Ling, C.M.; Hui, M.
Summary: Whereas high-flow nasal cannula use is gaining prevalence, its high gas flow raises concerns about aerosolization of infectious particles and spread of infection. This randomized controlled crossover non-inferiority trial ( N  = 20) evaluated the degree of environmental contamination by viable bacteria associated with the use of high-flow nasal cannula compared with conventional oxygen mask for critically ill patients with Gram-negative pneumonia. The results show that high-flow nasal cannula use was not associated with increased air or contact surface contamination by either Gram-negative bacteria or total bacteria, suggesting that additional infection control measures are not required.